Hubungan Kebersihan Gigi dan Mulut dengan Kejadian Karies Gigi Permanent Pada Siswa Kelas V SDN 7 Pedungan Denpasar Selatanm Tahun 2025 - Supariani, Ni Nyoman Dewi; Senjaya, Asep Arifin; Arini, Ni Wayan; Sirat, Ni Made; Fadila, Yulastri (Jurnal Kesehatan Gigi (Dental Health Journal), 2025)
Oral and dental hygiene is an important factor in the process of caries formation. 100% of school-age children, 60-90% experience dental caries. The purpose of this study was to determine the relationship between oral and dental hygiene and permanent dental caries in grade V students of SDN 7 Pedungan, South Denpasar in 2025. This study is a descriptive and analytical study of the relationship between oral and dental hygiene and the incidence of permanent dental caries. The sample in this study was grade V students of SDN 7 Pedungan, South Denpasar totaling 62 people. The results of the study on 62 respondents showed that the percentage of students' oral and dental hygiene was at most 76% good criteria, the average level of oral and dental hygiene was 0.93 with good criteria. The average of permanent dental caries of fifth grade students of SDN 7 Pedungan, South Denpasar in 2025 was 0.61, Sig value: 0.262 ( 0.05) meaning there is no relationship between dental and oral hygiene and permanent dental caries in fifth grade students of SDN 7 Pedungan, South Denpasar. The conclusion is that the level of dental and oral hygiene of fifth grade students at SDN 7 Pedungan is in good criteria, but students who have permanent dental caries are still relatively high and have not reached the national target.